Upaya Meningkatkan Motivasi Belajar Siswa dengan Metode Team Games Tournament (TGT) Terhadap Siswa Kelas XI SMA Negeri 1 Gowa - Nurul Mutmainna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to enhance students’ learning motivation through the application of the team games tournament (TGT) method in the 11th grade students at SMA N 1 Gowa. The study employs a classroom action research (CAR) design consisting of two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. The subjectof the study were 11th grade students at SMA N 1 Gowa. Data were collected through observation, interviews, and questionnaires, and then analyzed qualitatively and quantitatively. The results showed a significant increase in students’ learning motivation after the implementation of the TGT method. This method proved effective in creating a more interactive and competitive learning environment, therby boosting students’ enthusiasm and engagement in the learning process